2016
DOI: 10.1186/s13048-016-0229-8
|View full text |Cite
|
Sign up to set email alerts
|

GnRH agonist triggering affects the kinetics of embryo development: a comparative study

Abstract: BackgroundTo evaluate the effects of an ovulation triggering agent, human chorionic gonadotropin (hCG), versus a gonadotropin-releasing hormone agonist (GnRHa) on early embryo development in vitro using a time-lapse system.MethodsRetrospective analysis of a prospectively collected database. A total of 739 embryos from 152 infertile couples undergoing intracytoplasmic sperm injection cycles.Interventions : Embryo culture in a time-lapse incubator (EmbryoScope, Vitrolife, Göteborg, Sweden). Main Outcome Measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
(31 reference statements)
1
5
1
Order By: Relevance
“…The study showed that oocytes retrieved after GnRHa use were fertilized earlier, and the embryo cleavage until the six-cell stage was shorter in the GnRHa group compared with the hCG group. However, later development was similar between the two groups (22). The authors in this study did not provide data to show the clinical significance of these differences.…”
Section: Discussionmentioning
confidence: 60%
“…The study showed that oocytes retrieved after GnRHa use were fertilized earlier, and the embryo cleavage until the six-cell stage was shorter in the GnRHa group compared with the hCG group. However, later development was similar between the two groups (22). The authors in this study did not provide data to show the clinical significance of these differences.…”
Section: Discussionmentioning
confidence: 60%
“…As a result, the GnRHa group had a statistically higher number of FET cycles with blastocyst transfer (69.1% versus 55.6%; p =0.014) than the hCG group. Gurbuz et al (2016) showed that wherein time-lapse imaging of the embryos obtained from GnRHa, cleaved faster than the embryos obtained from hCG triggered cycles in antagonist protocols. It has been well established that early cleavage embryos results in a higher fraction of good-quality embryos and blastocysts ( Cruz et al, 2012 ; Wong et al, 2010 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Such technology has captured the imagination of practitioners as both a research tool (Costa-Borges et al, 2016;Hardarson et al, 2015;Mölder et al, 2015), comparing embryos resulting from various clinical conditions (Balakier et al, 2016;Gurbuz et al, 2016;Hashimoto et al, 2016;Kaihola et al, 2016;Lindgren et al, 2016), and as a potential prognosticator in clinical practice (Adamson et al, 2016;Chen et al, 2016;Kong et al, 2016;Liu et al, 2016;Milewski et al, 2015;Mizobe et al, 2016;Rubio et al, 2014;VerMilyea et al, 2014;Wu et al, 2016aWu et al, , 2016bYang et al, 2014), although some studies negate this (Freour et al, 2015;Wu et al, 2016aWu et al, , 2016b. Bronet et al (2015) even found distinctive morphokinetic differences between male and female embryos.…”
Section: Discussionmentioning
confidence: 99%